APLIKASI PEMILIHAN JURUSAN PADA PERGURUAN TINGGI MENERAPKAN FUZZY DECISION MAKING - Diana, Diana (Universitas Bina Darma, 2012)
This research aims to develops an application to select of college majors by using fuzzy decision making method. Set of alternatives discussed are engineering, Mathematics/Science, medical/pharmaceutical, economics/ management, psychology, law/sospol/communication, literature/arts/cultural and administrative/secretarial. While the set of criteria is language, logic/IT, science, and practice and social. Stages of to build this application are analyze, design, construction and implementation. Fuzzy decision making method are 1) Determine the decision alternatives, criteria set, and construct a hierarchical structure, 2) determine the weight of interest, the match weight, aggregating the weights of criteria and the degree of suitability of each alternative. 3) Selecting the optimal alternative to prioritize alternatives based on the aggregation of choosing alternative decision with the highest priority as the optimal alternative. Based on 10 times trial, the conclusion is the major that recommended to students is majoring in a degree of importance for each criterion based student ability. Keywords: Selection of Majors, University, Fuzzy Decision Making